A single field test evaluation for the assessment of the record power profile in cycling - Pujol, M.; Faiss, R. (Journal of Science and Cycling, 2021)
The validity of a single field test to produce a Record Power Profile (RPP) has not been investigated thoroughly in comparison with a RPP obtained during a full cycling season. We hypothesized that the values obtained from a single field test would match closely the values obtained during the season to define a RPP, and that cyclists would reach the highest power outputs (PO) during training sessions rather than in competition. The PO of eight male elite cyclists (maximal aerobic power 6.8±0.4 W/kg) was recorded during 12 months. They completed a Peak Power Profile test (PPP) during the competitive season including all-out efforts of 5 s, 12 s, and 30 s followed by 5 and 20 min. They were required to self-select their itinerary, pace, warm-up strategy and recovery efforts. An overall significant positive correlation was found between maximal power outputs obtained during the successive durations during the PPP and i) during training sessions (R2= 0.97) and ii) in competition (R2= 0.91). Conversely, peak PO during the PPP were higher than in competition only for short efforts (= 30 s). Training sessions represented the most common situation to achieve a record PO (55%) followed by the PPP (27.5%). This study reports the interest for a cyclist to perform a PPP to establish a RPP that would closely match potential values obtained during training (shorter efforts) or competition (longer efforts). Similar self-selected warm-up and recovery patterns in all cyclists illustrate a good reliability of the test. The underpinning strong motivation needed to reach ones peak PO over successive durations during one single field test may limit its validity over longer durations so that the 20 min peak power output may ideally be obtained from a separate field test.